DIVERSITY OF AGRITOURISM FARM OFFERS IN SELECTED SEASIDE LOCATIONS IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2022)
The main aim of the article is to evaluate the offers of agritourism farms located in selected seaside towns in the north-western part of Poland in terms of their diversity. The analysis was based on data from the websites of selected agritourism farms. The following methods were used: comparative analysis, SWOT analysis and SWOT/TOWS matrix. The analyzes show that agritourism farms on the Baltic Sea in Poland have a diversified offer both in terms of living conditions, as well as in terms of additional offer, including a typical agritourist offer. Agritourism farms located close to the sea gain their tourist attractiveness - the proximity of the sea is the main advantage of the offers of farms running agritourism activities in the north-western part of Poland.
Keywords: agritourism, agritourism product, seaside villages